SINTESIS FILM TUNGSTEN OKSIDA (WO3) DENGAN PENAMBAHAN METAL CO-KATALIS BESI (Fe) DAN APLIKASINYA PADA PENINGKATAN AKTIVITAS FOTOKATALITIK DEGRADASI ZAT WARNA METHYLENE BLUE MENGGUNAKAN CAHAYA MATAHARI - Burhanudin Syam; Hendri Widyandari (Youngster Physics Journal, 2014)
Degradation of dangerous pollutant with photocatalyst under solar or visible light radiation was a brilliant solution for environment pollution complication specifically for waste of liquid. So, we found a efficient photocatalyst which works at under wide spectrum from solar radiation. We report the synthesis of tungsten oxide/ferric oxide (WO3/Fe2O3) composite material and study the role value of weight ratio loaded for Fe co-catalyst material to crystal structure, morphologhy and the material chemical composition from WO3/Fe2O3 synthesis. And then, the photocatalyst would be application to degradation of methylene blue dye under visible light illumination.The synthesis of the WO3/Fe2O3 was deposited by photodeposition method followed by spray deposition technique on the glass substrate for controlling its morphology and chemical composition. Wearable four variations of mass ratio as data variables to determine the role of variations in the mass ratio of Fe co-catalyst material. The variations are pure WO3 or without Fe additive, WO3 with Fe additve 2%, 4%, and 6%. The composite’s microstructur and composition properties are characterized by SEM (Scanning Electron Microscope), EDX (Energy Dispersive X-ray Spectroscopy) and XRD (X-Ray Diffraction). Result showed, intensity from XRD’s graphic has decrease each additive co-catalyst Fe, so could be influence at WO3/Fe2O3 crystal size. The more quantity of additive weight ratio co-catalyst Fe againts WO3 then the crystal size of thin layer would be smaller. And then from methylene blue photodegradation result, the decrease intensity of C/C0 concentration  more faster and constant especially for 6% additive co-catalyst Fe. Then, the photodegradation sample has result more pure than 5 sample others. Keywords : WO3/Fe2O3, Photodegradation, photodeposition method, composite material, co-catalyst